Challenges faced by women entrepreneurs in South Asian countries using interpretive structural modeling - Reena Agrawal; Priti Bakhshi; Arti Chandani; Ramona Birau; Suhan Mendon (Cogent Business & Management, 2023)
Promoting women's economic participation and empowerment is essential for sustainable development in South Asian Countries. Studies have established that women entrepreneurs in South Asia face a noteworthy challenge with many lacking formal education, lack of entrepreneurship education, capital, skilled and trained manpower, management skills, networking, infrastructural support, fear of failure, gender discrimination, and loaded with family responsibilities. This research aims to evaluate the contextual relationships among identified key challenges and develop a hierarchical framework of key challenges for addressing barriers to promote women entrepreneurship in South Asian Countries. The primary study was conducted using Interpretive Structural Modelling on 31 women entrepreneurs from India, Nepal, Sri Lanka, Pakistan, and Bangladesh. The study proposed that multi-dimensional efforts are needed to ensure that women have equal access to economic opportunities and can fully participate in and contribute to the region's economic development.
Keywords: 650; business; capital; challenges; education; fear of failure; financial institutions; gender issues; women entrepreneurs; women's economic participation